Synergetic functional properties of two-component single amino acid-based hydrogels. Issue 42 (30th July 2015) - Fichman, Galit; Guterman, Tom; Adler-Abramovich, Lihi; Gazit, Ehud
Abstract : Hybrid hydrogels composed of the Fmoc-Tyr and Fmoc-DOPA building blocks present mechanical rigidity and redox activity. Abstract : The formation of hydrogels by low molecular weight building blocks results in important supramolecular assemblies for technological applications. N -modified amino acids are especially interesting components for the organization of such structures due to their high association efficiency, inherent biocompatibility, and structural diversity. Fluorenylmethoxycarbonyl (Fmoc)-modified tyrosine (Fmoc-Tyr) has been extensively studied as a notably simple yet highly efficient hydrogelator. Here, we present the ability to use a combination of Fmoc-Tyr and catechol-containing Fmoc-3, 4-dihydroxyphenylalanine (Fmoc-DOPA) to form a functional two-component hydrogel which combines the physical characteristics of the Fmoc-Tyr hydrogels and the functionality of the catechol groups. We demonstrate that a combination of the two building blocks results in the rapid formation of three-dimensional self-supporting gels. Rheological analysis indicated that the observed hybrid gel has a very high storage modulus, of the same order of magnitude as that of the Fmoc-Tyr gel. In addition to the envisioned mechanical properties, the combined gel also displayed a clear silver ion reduction activity. Taken together, we illustrate the ability to utilize two-component gels to achieve synergetic properties, combining rigidity and functionality.